Heavy metal contamination in retailed food in Bangladesh: a dietary public health risk assessment - Begum, R.; Akter, R.; Sinh Dang-Xuan; Islam, S.; Siddiky, N.A.; Uddin, A.S.M.A.; Mahmud, A.; Sarker, M.S.; Grace, Delia; Samad, M.A.; Lindahl, Johanna F. (Frontiers Media, 2023)
Introduction: Contamination with heavy and toxic metals along the food value chain is a public health concern in Bangladesh.